The philosophy of Georg Simmel - Beiser, Frederick C., 1949- author. aut Link Link Link
1 online resource.
Keywords: "In this ground-breaking work, Frederick Beiser argues that Georg Simmel was one of the foremost yet overlooked philosophers of the late nineteenth and early twentieth centuries. Whilst Simmel's work was crucial in laying foundations for sociology, his several books, including The Philosophy of Money, were deeply philosophical. Simmel's doctorate was on Kant's philosophy and that his intellectual outlook was greatly influenced by his lifelong love of philosophy. It is this philosophical Simmel that Frederick C. Beiser, a renowned scholar of German philosophy, explores in this fascinating and important book. Beginning with a helpful overview of Simmel's early intellectual life, Beiser considers the formation of Simmel's sociology and his views on ethics, before examining his theories of historical knowledge; the arguments contained in his most important work, The Philosophy of Money; the role of Kant's philosophy in his thinking; his critique of pessimism and his philosophy of religion. The second part of the book explores the deeper philosophical importance of Simmel's work, by considering his theories of the method and essence of philosophy, the philosophy of life and his important work on aesthetics. An outstanding and path-breaking book, The Philosophy of Georg Simmel will be of interest to students and researchers in philosophy and sociology alike, particularly those studying nineteenth century philosophy and the history of sociology"-- Provided by publisher.